THE IMPACT OF SOCIAL MEDIA ON TEENAGERS - N. Q. Yesengeldiyeva; E. V. Yugay (Web of Journals Publishing, 2024)
This paper discursively examines how social media influences teenagers, focusing on the content, language, and behavioral changes that result from social media use. It highlights how internet slang and the portrayal of human frailties on social media platforms affect teenagers' behavior and interaction with technology. Social media affects teenagers in many ways, including their online habits, sleep, how they communicate, their language skills, schoolwork, ability to finish tasks, and their need for instant things. The study concludes that social media plays a significant role in shaping high school students' behaviors. Recommendations include the creation of guidelines for selecting social media content as teaching materials, a holistic assessment of social media's effectiveness in education, and interventions to control excessive social media use.
Keywords: social media, influences, social awareness, teenagers, behavior.